2010
DOI: 10.1007/s10298-010-0590-5
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation des marqueurs sériques enzymatiques du coeur chez les lapins traités par Phyllanthus amarus (Euphorbiacées)

Abstract: Pendant quatre semaines de traitement et une semaine sans traitement, des évaluations in vivo des marqueurs sériques du coeur de lapin, traités par un extrait aqueux de Phyllanthus amarus, ont permis de déterminer l'activité enzymatique sérique de la glutamo-oxaloacétique transaminases (GOT), la lactate déshydrogénase (LDH) et la créatine phosphokinase (CPK). Les lapins traités par voie intrapéritonéale avec différentes doses variant de 0 à 100 mg/kg de poids corporel ont permis d'avoir, par rapport aux valeur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
3
1
1
Order By: Relevance
“…These results are contrary to those of Coulibaly et al [27] who showed that the aqueous extract of Phyllanthus amarus reduced the CPK level over time and induced a cardioprotective effect. The activities of transaminases (AST) and LDH decreased, while that of CPK-MB increased in the groups treated at the dose of 600 mg/kg body weight over time.…”
Section: Discussioncontrasting
confidence: 99%
“…These results are contrary to those of Coulibaly et al [27] who showed that the aqueous extract of Phyllanthus amarus reduced the CPK level over time and induced a cardioprotective effect. The activities of transaminases (AST) and LDH decreased, while that of CPK-MB increased in the groups treated at the dose of 600 mg/kg body weight over time.…”
Section: Discussioncontrasting
confidence: 99%
“…Les valeurs normales de l'urée, de la créatinine ainsi que l'absence de glucose, de corps cétoniques dans les urines suggèrent que cet extrait n'a pas modifié la structure et les fonctions rénales. En effet, des travaux ont montré que ces valeurs sont élevées en cas d'altération des reins (Coulibaly et al, 2007).…”
Section: Discussionunclassified
“…The doses evaluated were below the maximal tolerated doses of Phyllanthus amarus administrated i.p. [ 24 ].…”
Section: Methodsmentioning
confidence: 99%